The genetic resources of Taxus baccata L. in Mustafakemalpaşa and Karacabey/Turkey - Dikeş, Seren; Yılmaz, Mustafa; Kalkan, Mehmet (My University, 2021)
The population of Taxus baccata L. (Yew Tree), which is a valuable tree in our country, is graduallydecreasing and it is under protection in places. Generally, it is scattered in the shady areas and northern aspects of forestlandscapes. T. baccata, a natural and medicinal plant for the flora of Bursa, has small populations in riverbeds andhillsides in Mustafakemalpaşa and Karacabey. In this study main objectives were the finding of natural distributionareas and the individuals at different altitudes in the districts surveyed, habitat characteristics of individuals, thecollection of ethnobotanical information about the species from the local people. In the field trips, major characteristicsof each tree and its site were recorded including diameter, height, land use, the views of the individuals, aspects,altitudes, and coordinates. After the result of field trips, 172 trees were recorded in Mustafakemalpaşa (133 trees) andKaracabey (39 trees). The largest part of the trees was forest land (%95,4) and north aspects (%54,7). The lowest andthe highest elevation of the species in the region were 192 m and 1034 m, respectively. The silvicultural tendingtreatments should be applied for the conservation of yew tree populations and individuals. There are difficulties in theregeneration and reproduction of yew trees due to limited germination and competing vegetation in the site. On theother hand, yew trees growing in sensitive sites are expected to be most affected by climate change. Therefore, there is aneed for special public awareness and conservation studies for the species.
Keywords: Biyoloji; Bahçe Bitkileri; Biyoloji Çeşitliliğinin Korunması